Chemometric Assisted Development and Validation of a Stability-indicating LC Method for Determination of Related Substances in Haloperidol Decanoate Injection - Babu, Sudheer Kolla; Rao, Madhusudhan Vallabhaneni; Babu, Srinivasa Puttagunta; Chakka, Murthy Veera Venkata Satyanarayana (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: Haloperidol decanoate injection is a phenyl butyl piperadine derivative with antipsychotic, neuroleptic, antiemetic effects and has multiple related substances as process and degradant impurities. Objectives: This study focuses on chemometric assisted liquid chromatographic approach to develop a stability indicating impurity profile of Haloperidol decanoate injection. Methodology: Dual experimental designs (combined mixture I-optimal design and response surface historical data design) were employed to resolve all thirteen known impurities of Haloperidol decanoate. Chromatographic separation was achieved on a Hypersil BDS C18 (100 x 4.0 mm) 3-µm column to attain separation of related compounds. Results: The optimum conditions for the chromatographic system resulted in a mobile phase consisting of tetra butyl ammonium hydrogen sulphate/ 1-decane Sulphonate sodium buffer solution and acetonitrile with linear gradient elution at a flow rate of 1.4 mL/min. Selectivity, forced degradation, linearity, accuracy and precision were demonstrated in a range of 0.75-30.0 µg/mL. Conclusion: The optimized method was able to resolve the ghost peak observed because of gradient change of mobile phase and is able to separate both polar and non-polar impurities within 60 min, in single method, with resolution of more than 2.0 between adjacent impurities. The inter-day precision for all impurities and haloperidol decanoate were evaluated and found to have a % RSD of less than 10.
Keywords: Design of Experiments; Haloperidol decanoate Injection; Stability indicating method; DoE aided chromatographic method development; Artifact optimization